Seasonal dynamics of common ground beetles (Coleoptera: Carabidae) along an urbanisation gradient near Sorø, Zealand, Denmark - Elek, Zoltán; Howe, Andy; Enggaard, Mattias; Lövei, Gábor (Entomologica Fennica, 2017)
The seasonal activity of six carabid species (Nebria brevicollis, Carabus nemoralis, C. hortensis, C. coriaceus, Pterostichus melanarius and Abax parallelepipedus) was studied along an urbanisation gradient (rural forest – suburban forest – forest fragments in urban park) in Sorø, Denmark, during April–October 2004 and 2005.Two groups were identified: 1) Species with constant seasonality, in which seasonal activity profiles did not differ along the gradient (C. hortensis, C. coriaceus, and A. parallelepipedus); 2) Species with flexible seasonality,with remarkable differences along the gradient and between the years (C. nemoralis, N. brevicollis and P. melanarius). In four out of six studied species, 2005 was less favourable than 2004. Spring activity in the urban habitat started earlier than in the suburban or forested ones. A better understanding of urban green infrastructures in biodiversity assessments may need the study of seasonality in order to distinguish whether the bioindicator’s responses are to habitat quality or stochastic seasonal events.